(untitled) (Annals of Medical Research, 2021)
Aim: To compare the results of endoscopic endonasal dacryocystorhinostomy (endonasal-DCR) and external dacryocystorhinostomy (external-DCR) and to evaluate patient satisfaction after the procedures. Materials and Methods: Patients who underwent dacryocystorhinostomy (DCR) were examined prospectively. Demographic data, follow-up periods, success rates and complications were recorded. A patient satisfaction questionnaire was used for subjective evaluation.Results: The mean age of external-DCR patients was 53.14± 3.41 while it was 52.05 ± 2.15 years years in patients who underwent endonasal-DCR procedure (p=0.074). The follow-up period ranged from 6 to 30 months. The success rates in the endonasal-DCR and external-DCR operations were 91.1% and 92.3%, respectively. The patient satisfaction was better in the endonasal-DCR as compared to external-DCR. Compared to external-DCR (17%), none of the endonasal-DCR patients had visible scars. The time it takes patients to return to daily routine was 12.4 ± 2.71 days in external-DCR and, 5.10 ± 0.99 days in endonasal-DCR (p0.001).Conclusion: Although the success rates are better in external-DCR, the patient satisfaction was significantly higher, and the recovery times were significantly lower in endonasal-DCR.